Winged bean [Psophorcarpus tetragonolobus (L.) DC] seeds as an underutilised plant source of bifunctional proteolysate and biopeptides - Chay, Shyan Yea; Ebrahimpour, Afshin; Abdul Hamid, Azizah; Bakar, Jamilah; Syed Muhammad, Sharifah Kharidah; Saari, Nazamid (Royal Society of Chemistry, 2014)
Hypertension is one of the major causes of cardiovascular-related diseases, which is highly associated with angiotensin-I-converting enzyme (ACE) activity and oxidative stress. In this study, winged bean seed (WBS), a potential source of protein, was utilised for the production of bifunctional proteolysate and biopeptides with ACE inhibitory and antioxidative properties. An enzymatic approach was applied, coupled with pretreatment of shaking and centrifuging techniques to remove endogenous ACE inhibitors prior to proteolysis. ACE inhibition reached its highest activity, 78.5%, after 12 h proteolysis while antioxidative activities, determined using assays involving DPPH˙ radical scavenging activity and metal ion-chelating activity, reached peaks of 65.0% and 65.7% at 8 h and 14 h, respectively. The said bioactivities were proposed to share some common structural requirements among peptides. A two-dimensional approach was employed for characterisation of effective peptides based on hydrophobicity, using RP-HPLC, and isoelectric property, using isoelectric focusing technique. Results revealed that acidic and basic peptides with partially higher hydrophobicity provided higher ACE inhibition activity than did neutral peptides. Finally, by using Q-TOF mass spectrometry, two peptide sequences (YPNQKV and FDIRA) with ACE inhibitory and antioxidative activities were successfully matched with a database. This study indicates that the WBS proteolysate can be a potential bifunctional food ingredient as the identified biopeptides demonstrated both ACE inhibitory and antioxidative activities in vitro.